URIP IKU URUP: PROGRAM KONSELING TEMAN SEBAYA SEBAGAI UPAYA MENINGKATKAN MENTAL HEALTH AWARENESS PADA SISWA DI SMK BERBUDI YOGYAKARTA - Wulandari, Tiyas; Iqbal, Maliqazuhra; Khasna, Naeri; Nufus, Anisa Zakiatun; Hidayah, Meli Nur; Rizqia, Ayu Gigih (Sekolah Tinggi Ilmu Ekonomi AMA, 2024)
Mental health is an important aspect in the well-being of individuals, especially students in a school setting. However, awareness of the importance of mental health is often low among students which negatively impacts their development. This study aims to increase mental health awareness at SMK Berbudi Yogyakarta through a peer counseling program, utilizing the Javanese philosophy of “Urip Iku Urup.” The research method used was One Group Pre-Test Post-Test Design, in which the experimental group was given a Pre-Test scale before the intervention and a Post-Test scale after the intervention. The intervention included training and role play, as well as counseling practices using MHA Board Games and Mindful Mixer Games media. The results showed a significant increase in students' mental health awareness, with a pre-test mean score of 40.04 and a post-test mean score of 47.96. Thus, it can be concluded that the peer counseling program is effective in increasing students' mental health awareness at SMK Berbudi Yogyakarta.